Evaluasi Prestasi Atlet Gulat Pelatda Propvinsi Jawa Tengah - Wati, Kharisma; Setyawati, Heny (Universitas Negeri Semarang, 2023)
The objective in this study is to know about the wrestling achievement development at Regional Training Center in Central Java. This study is qualitative. The method of collecting the data was using documentation, observation, and interview. The research analysis used reduction technique. The results obtained some informations that (1) financial support is appropriate, but for management and funding is not efficient, (2) the existence of an integrated sports policy organization and structure are clear, (3) the training for childhood has been carried out well, (4) talent identification and development has gone well, but the senior athletes lack of achievements, (5) the reward and support system in the post-career period is already running well, but for BPJS facilities is not optimal, (6) sports infrastructure: training facilities are incomplete and some of those still rent, (7) providing trainers, coaching and training quality in the recruitment of trainers are according to the recommendations of branch administrators and certified, (8) quality of competition: national and international standards are still in the submission stage, 9) innovation in coaching, namely conducting physical and psychological tests routinely, and (10) the media of sponsorship has collaborated with several media, both printed and electronic media. The necessity in improving the facilities and infrastructures for training, maximizing the appreciation and support for athletes who have achievements, also setting the national and international competition standards.